Development of trade in recyclable raw materials: Transition to a circular economy - Olga Lingaitiene; Aurelija Burinskiene (Economies, 2023)
Mechanisms for sectoral change in the economy are being used to move towards a circular economy. Trade in recycled raw materials could contribute to circular economy development and is treated as the main circular indicator used to monitor progress toward a circular economy. However, the research area surrounding the transition to a circular economy lacks adequate tools, as until now, the circular economy has been investigated from an evolutionary and ecological perspective. In the article, the authors conduct a study identifying important variables for trade in recycled raw materials as the main indicator of CE development. The authors propose a two-step methodology for researching the links between main trade in recyclables and circular economy indicators. The authors found correlations between trade in recyclables and private investments in circular economy sectors. The authors used panel data analysis, compiled a regression matrix, and formed a dynamic regression model. The statistical tests showed that the formed regression model has no significant autocorrelation and heteroscedasticity. The framework can be applied in practice to serve policymakers and the academic community interested in analyzing the move toward a circular economy and its main circular indicators.
Keywords: 330; circular economy; trade; recyclables; EU